1994
DOI: 10.1073/pnas.91.15.6885
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the Anopheles gambiae complex suggests genetic introgression between principal malaria vectors.

Abstract: The six Afrotropical species of mosquitoes comprising the Anopheks gambiae complex include the most efficient vectors of malaria in the world as well as a nonvector species. The accepted interpretation of evolutionary relationships among these species is based on chromosomal inversions and suggests that the two principal vectors, A. gambiae and Anopheks arabiensis, are on distant branches of the phylogenetic tree. However, DNA sequence data indicate that these two species are sister taxa and suggest gene flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
80
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 20 publications
8
80
0
1
Order By: Relevance
“…Phylogenetic approaches to resolving taxa relationships in these species have been hampered by high intraspecific and low interspecific variation (Besansky et al, 1994;Krz -ywinski et al, 2001). Previous studies of partial sequence of mitochondrial DNA have shown that large numbers of haplotypes are shared between A. gambiae, A. arabiensis and A. bwambae Thelwell et al, 2000;Donnelly et al, 2001), but whether this is a result of introgression or retention of ancestral polymorphisms is unresolved Thelwell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic approaches to resolving taxa relationships in these species have been hampered by high intraspecific and low interspecific variation (Besansky et al, 1994;Krz -ywinski et al, 2001). Previous studies of partial sequence of mitochondrial DNA have shown that large numbers of haplotypes are shared between A. gambiae, A. arabiensis and A. bwambae Thelwell et al, 2000;Donnelly et al, 2001), but whether this is a result of introgression or retention of ancestral polymorphisms is unresolved Thelwell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Yet recent studies of Drosophila and Anopheles species (e.g., refs. [2][3][4][5], suggest that introgression is not necessarily rare or inconsequential; indeed, it may be advantageous (2). This alternative viewpoint is not new.…”
mentioning
confidence: 99%
“…gambiae-An. arabiensis relationship inferred from other markers, especially the paraphyletic, intertwining mtDNA (2,14), has been interpreted as reflecting the flow of nuclear and mtDNA sequences across species boundaries, rather than the persistence of ancestral alleles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this hypothesis, limited genetic introgression has been observed among members of the An. gambiae complex (Besansky et al 1994, Kamau et al 1998 After all the sequences were organized and all identical sequences removed from the pool, the remaining 105 unique entries were used to construct a similarity tree (Fig. 1, nucleotide distances estimated a: the species included in this table are those in which Plasmodium parasites have been detected by direct microscopic observation, immunological and molecular approaches.…”
Section: Its2 Of Latin American Anophelinesmentioning
confidence: 99%